Pseudoxanthoma elasticum. Case presentation - Graciela Caridad Cabrera Acea; Ana Dolores López Marquet; María Julia Cabrera Pereda (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
The case of a female patient of 23 years of age is presented. The patient attended to the dermatology consultation in her health area for skin lesions in the neck area, of 10 years of evolution with new lesions after three years in different parts of her body (armpits, periumbilical, vaginal and rectal regions). These lesions present an aspect similar to orange skin, surrounded by yellow papules. the diagnosis was pseudoxanthoma elasticum after the clinical and histopathological analysis, and the perimetry. We present this case since this is an infrequent disease and for the importance of an early diagnosis of skin lesions in a systemic disease.